2015
DOI: 10.1007/s10439-015-1253-3
|View full text |Cite
|
Sign up to set email alerts
|

Vascularization in Bone Tissue Engineering Constructs

Abstract: Vascularization of large bone grafts is one of the main challenges of bone tissue engineering (BTE), and has held back the clinical translation of engineered bone constructs for two decades so far. The ultimate goal of vascularized BTE constructs is to provide a bone environment rich in functional vascular networks to achieve efficient osseointegration and accelerate restoration of function after implantation. To attain both structural and vascular integration of the grafts, a large number of biomaterials, cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
199
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(202 citation statements)
references
References 122 publications
2
199
0
1
Order By: Relevance
“…6). Without prevascularization of the scaffold, it may take too long to form the vasculature upon implantation which would result in an ischemic condition before the desired neo-bone could form and integrate into the defect site [55]. Absence of a uniform vasculature is especially detrimental for scaffolds of clinically relevant sizes.…”
Section: Discussionmentioning
confidence: 99%
“…6). Without prevascularization of the scaffold, it may take too long to form the vasculature upon implantation which would result in an ischemic condition before the desired neo-bone could form and integrate into the defect site [55]. Absence of a uniform vasculature is especially detrimental for scaffolds of clinically relevant sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Porosity, swelling capacity, water absorption, compressive strength and compressive modulus analysis indicated that the physical properties of the scaff old met the basic requirements for use in tissue engineering [30][31][32][33] (Tables 1 and 2). One hour after the start of the experiment, the pH was approximately 7.0.…”
Section: Porosity Swelling Capacity Water Absorption Capacity Mechmentioning
confidence: 99%
“…To accelerate the engraftment and improve the survival of such engineered bone tissues, the focus has recently been directed toward their prevascularization. [3][4][5][6][7][8][9] Additionally and equally important, the acquiring of knowledge on vascularization of bone mimicking tissues in combination with novel tailorable biomaterials and advanced 3D manufacturing processes will make the creation of physiologically relevant in vitro bone models become tangible. Such models would allow for the study and testing of healing inducing treatments under fully defi ned and reproducible experimental conditions.…”
mentioning
confidence: 99%